Numerical simulation design and optimization of regional cathodic protection in a large oil and gas station - Wang, Rong; Luo, Jiqing; He, Sha; Deng, Weilin; Deng, Yonggang; Yang, Qingxian; Hu, Peng; Shen, Xurui; Gan, Tiansiyu (Frontiers in Chemical Engineering, 2025)
IntroductionWith increasing attention from both national authorities and the oil and gas industry to corrosion protection, regional cathodic protection (CP) design and optimization have become essential for ensuring the safe operation of large oil and gas stations.MethodsA representative large station was selected for detailed investigation, including the collection of basic information and operational conditions. Environmental medium and electrochemical tests were performed to determine the most suitable anode type. Based on the test results, a numerical simulation model of a deep-well anode CP system was established to support regional CP design and optimization.ResultsThe simulation produced optimized design parameters, including the number and spatial arrangement of deep-well anodes and their required output currents. Using these results, a practical CP scheme tailored for large oil and gas stations was proposed. The optimized configuration, refined through six iterative simulations, achieved the required CP potential distribution and improved uniformity across the protected region.DiscussionThis study addresses limitations of traditional CP design approaches, such as insufficient optimization of anode layouts and inadequate consideration of current shielding effects. By overcoming these issues, it provides both theoretical insights and practical strategies to guide more effective regional CP engineering.